The Effect of Growth Opportunity, Net Working Capital and Leverage on Cash Holding - Angelika Agustina Silaban; Benarda (Formosa Journal of Sustainable Research, 2023)
The purpose of this study is to determine the effect of Growth Opportunity, Net Working Capital, and Leverage on Cash Holding in the Real Estate Property Sector Listed on the Indonesia Stock Exchange (IDX). Companies in the property and real estate sector listed on the Indonesia Stock Exchange from 2017 to 2021 are the study population. In this study, 180 samples from 36 companies were sampled using purposive sampling method and observed for 5 years. In this study, this type of research used a quantitative approach using multiple linear regression analysis techniques using the e-views application 9. The results showed that simultaneously growth opportunity, net working capital and leverage have an effect on cash holdings. Partially, growth opportunity has no effect on cash holding, while net working capital and leverage have an effect on cash holding